2014
DOI: 10.1007/s12149-014-0863-4
|View full text |Cite
|
Sign up to set email alerts
|

A randomized study of the effect of carbonated water prior to myocardial SPECT

Abstract: Objective In myocardial perfusion single-photon emission computed tomography (SPECT), abdominal activity often interferes with the evaluation of perfusion in the inferior wall, especially after pharmacological stress. In this randomized study, we examined the effect of carbonated water intake versus still water intake on the quality of images obtained during myocardial perfusion images (MPI) studies. Methods A total of 467 MIBI studies were randomized into a carbonated water group and a water group. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
(11 reference statements)
0
6
1
Order By: Relevance
“…Thus, the decrease in the MYO:EXC ratio in the delayed stress studies when the combined intervention was given may have been impacted by this natural biologic process. Overall, the MYO:EXC ratio was higher than the recommended target to non-target ratio of 2:1 and was also higher than results from previous studies [3,5,6,12,15,16,20,25]. It is suspected that the differences in imaging times between the studies played a role in the discrepancies of the ratio between studies.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…Thus, the decrease in the MYO:EXC ratio in the delayed stress studies when the combined intervention was given may have been impacted by this natural biologic process. Overall, the MYO:EXC ratio was higher than the recommended target to non-target ratio of 2:1 and was also higher than results from previous studies [3,5,6,12,15,16,20,25]. It is suspected that the differences in imaging times between the studies played a role in the discrepancies of the ratio between studies.…”
Section: Discussioncontrasting
confidence: 57%
“…However, there was a small decrease of 0.03 and 0.02 in the MYO:EXC ratio in the early and delayed stress studies respectively. In a study of the effect of carbonated water prior to myocardial SPECT, Vermeltfoort et al found persistence of interfering infra-cardiac activity in some patients who consumed carbonated water [5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations